Praca osób z głębszą niepełnosprawnością intelektualną jako źródło emancypacji w kontekście samorealizacji - Ramik-Mażewska, Irena (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The problem of normalization, autonomy and self-determination of people with intellectual disabilities in special education has already taken its place. The consequence of this continuing discourse is the personal nature of disability, international, timeless declarations and modifications of already established rights. Recently, the emancipatory trend is gaining in importance in this discourse. It remains in close correlation with the primary objective of educating people with intellectual disabilities which is comprehensive preparation for life. It is a form of conscious self-reliance, self-knowledge and capacity to take autonomous action. One of the areas of development of self-reliance is work. The resulting interpersonal and intrapersonal experiences can become the path to emancipation. Sometimes, one that goes beyond the standards of rehabilitation.